Tonsuritermes, a new soldierless termite genus and two new species from South America (Blattaria: Isoptera: Termitidae: Apicotermitinae) - Constantini, Joice P.; Carrijo, Tiago Fernandes; Palma-Onetto, Valeria; Scheffrahn, Rudolf; Carnohan, Lucas Paul; Šobotník, Jan; Cancello, Eliana M. (Zootaxa, 2018)
A new genus, Tonsuritermes Cancello & Constantini gen. nov., is described from South America. The main morphological features of the new genus are a remarkable frontal gland and protibia with two rows of spine-like bristles. Two new species of Tonsuritermes are described: T. tucki Cancello & Constantini sp. nov. and T. mathewsi Cancello & Constantini sp. nov. Comparisons, measurements, a map, histology of the frontal gland, and illustration of all fundamental morphological aspects are provided.